The Effect of Bad Loans on Working Capital in the Rahmat Sejahtera Savings and Loan Cooperative Palopo - S. Sudirman; Henri Fauli; Umar Hi Salim (Golden Ratio of Mapping Idea and Literature Format, 2026)
The effect of bad loans on working capital at the Rahmat Sejahtera Palopo savings and loan cooperative. The purpose is to find out and analyze the influence of bad loans on working capital in the Rahmat Sejahtera Palopo savings and loan cooperative. This study uses  a proportional random sampling method, the data used in this study is primary data in the form of secondary data.  The results of this study show that bad loans do not have a significant effect on working capital in the Rahmat Sejahtera Palopo savings and loan cooperative, this is evidenced by the results of data analysis explaining that  the bad loan variable (X) has no effect on the working capital in the Rahmat Sejahtera Palopo savings and loan cooperative, the value of the correlation coefficient (R) is 54.5%, this shows that the relationship between the free variable, namely bad loans and working capital in the Rahmat Sejahtera Palopo savings and loan cooperative,  has a weak relationship because it is close to 0 (zero) but still has a positive correlation, meaning that if the company tightens its collection of receivables to customers, it will increase working capital, the result of the determination coefficient value (R2) of 29.7% showed that the influence or contribution of the non-bad loan variable (x) on working capital (Y) in the Rahmat Sejahtera Palopo savings and loan cooperative was 29.7% and the remaining 70.3% was influenced by other factors or variables that were not studied in this study, The results of the t-test were conducted to see and partially measure the influence of the free variable (X) on the bound variable (Y).